Systemic therapy treatment patterns in patients with advanced non-small cell lung cancer (NSCLC): PIvOTAL study - Castro, Javier de; Thomas, Michael (European journal of cancer care, 2017)
The aim of this multinational retrospective cohort study, conducted at academic and community oncology centres, was to describe real-world treatment patterns for patients with a confirmed diagnosis of advanced/metastatic (stage IIIB/IV) non-small cell lung cancer (NSCLC) who initiated first-line systemic therapy from January 2011 through June 2014. The study included 1265 patients in Italy, Spain, Germany, Australia, Korea, Taiwan and Brazil. The proportion of patients with squamous versus non-squamous NSCLC was approximately 20% versus 75%, and associated patient demographic characteristics were similar in all countries, excepting race. Patients with squamous NSCLC were predominantly male and current/ex-smokers. Biomarker tests were performed for the majority of patients with non-squamous NSCLC, ranging from 54% (Brazil) to 91% in Taiwan, where, of those tested, 68% with non-squamous NSCLC had positive epidermal growth factor receptor (EGFR)-mutation status; in other countries the EGFR-positive percentages ranged from 17% (Spain/Brazil) to 40% (Korea). Platinum-based regimens were the most common first-line therapy in all countries except Taiwan, where gefitinib was the most common first-line agent. Median overall survival ranged from 9.3 months (Brazil) to 25.5 months (Taiwan). The diagnostic and treatment patterns recorded in this study were heterogeneous but largely in line with NSCLC guidelines during the study period.